Facile chemical routes to mesoporous silver substrates for SERS analysis - Tastekova, Elina A.; Polyakov, Alexander Yu; Goldt, Anastasia E.; Sidorov, Alexander V.; Oshmyanskaya, Alexandra A.; Sukhorukova, Irina V.; Shtansky, Dmitry V.; Grünert, Wolgang; Grigorieva, Anastasia V. (Beilstein Journal of Nanotechnology, 2018)
Mesoporous silver nanoparticles were easily synthesized through the bulk reduction of crystalline silver(I) oxide and used for the preparation of highly porous surface-enhanced Raman scattering (SERS)-active substrates. An analogous procedure was successfully performed for the production of mesoporous silver films by chemical reduction of oxidized silver films. The sponge-like silver blocks with high surface area and the in-situ-prepared mesoporous silver films are efficient as both analyte adsorbents and Raman signal enhancement mediators. The efficiency of silver reduction was characterized by X-ray diffraction and X-ray photoelectron spectroscopy. The developed substrates were applied for SERS detection of rhodamine 6G (enhancement factor of about 1–5 × 105) and an anti-ischemic mildronate drug (meldonium; enhancement factor of ≈102) that is known for its ability to increase the endurance performance of athletes.
Keywords: meldonium; mesoporous silver substrates; silver oxide; surface-enhanced Raman spectroscopy

(untitled) - Li, W.; Liu, J.; Zhao, D. (Nat. Rev. Mater., 2016)

(untitled) - Peng, S.; Sun, Y. (Chem. Mater., 2010)

(untitled) - Linares, N.; Silvestre-Albero, A. M.; Serrano, E.; Silvestre-Albero, J.; García-Martínez, J. (Chem. Soc. Rev., 2014)

(untitled) - Kuai, L.; Wang, J.; Ming, T.; Fang, C.; Sun, Z.; Geng, B.; Wang, J. (Sci. Rep., 2015)

(untitled) - Yang, S.; Luo, X. (Nanoscale, 2014)

(untitled) - Zhang, R.; Olin, H. (Materials, 2014)

(untitled) - Okman, O.; Kysar, J. W. (J. Alloys Compd., 2011)

(untitled) - Sapoletova, N. A.; Martynova, N. A.; Napolskii, K. S.; Eliseev, A. A.; Lukashin, A. V.; Kolesnik, I. V.; Petukhov, D. I.; Kushnir, S. E.; Vassilieva, A. V.; Grigoriev, S. V.; Grigoryeva, N. A.; Mistonov, A. A.; et al. (Phys. Solid State, 2011)

(untitled) - Yin, X.; Xue, Z.; Liu, B. (J. Power Sources, 2011)

(untitled) - Cox, M. E.; Dunand, D. C. (Mater. Sci. Eng., A, 2011)

(untitled) - Quan, X.; Fischer, L. M.; Boisen, A.; Tenje, M. (Microelectron. Eng., 2011)

(untitled) - Au, L.; Chen, Y.; Zhou, F.; Camargo, P. H. C.; Lim, B.; Li, Z.-Y.; Ginger, D. S.; Xia, Y. (Nano Res., 2008)

(untitled) - Krishna, K. S.; Sandeep, C. S. S.; Philip, R.; Eswaramoorthy, M. (ACS Nano, 2010)

(untitled) - Wen, D.; Liu, W.; Haubold, D.; Zhu, C.; Oschatz, M.; Holzschuh, M.; Wolf, A.; Simon, F.; Kaskel, S.; Eychmüller, A. (ACS Nano, 2016)

(untitled) - Muench, F.; Schaefer, S.; Hagelüken, L.; Molina-Luna, L.; Duerrschnabel, M.; Kleebe, H.-J.; Brötz, J.; Vaskevich, A.; Rubinstein, I.; Ensinger, W. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Josell, D.; Levin, I.; Moffat, T. P. (J. Electrochem. Soc., 2015)

(untitled) - Muehlethaler, C.; Leona, M.; Lombardi, J. R. (Anal. Chem., 2016)

(untitled) - Robinson, A. M.; Harroun, S. G.; Bergman, J.; Brosseau, C. L. (Anal. Chem., 2012)

(untitled) - Sidorov, A.; Vashkinskaya, O.; Grigorieva, A.; Shekhovtsova, T.; Veselova, I.; Goodilin, E. (Chem. Commun., 2014)

(untitled) - Gu, Y.; Zhang, L.; Yang, J. K. W.; Yeo, S. P.; Qiu, C.-W. (Nanoscale, 2015)

(untitled) - Chen, T.; Reinhard, B. M. (Adv. Mater., 2016)

(untitled) - Yorov, K. E.; Grigorieva, A. V.; Sidorov, A. V.; Polyakov, A. Yu.; Sukhorukova, I. V.; Shtansky, D. V.; Grünert, W.; Goodilin, E. A. (RSC Adv., 2016)
Correction: doi:10.1039/C6RA90035F

(untitled) - Yang, Z.; Zhang, L.; You, H.; Li, Z.; Fang, J. (Part. Part. Syst. Charact., 2014)

(untitled) - Zhang, Q.; Large, N.; Nordlander, P.; Wang, H. (J. Phys. Chem. Lett., 2014)

(untitled) - Agarwal, N. R.; Tommasini, M.; Fazio, E.; Neri, F.; Ponterio, R. C.; Trusso, S.; Ossi, P. M. (Appl. Phys. A, 2014)

(untitled) - Lyu, L.-M.; Wang, W.-C.; Huang, M. H. (Chem. – Eur. J., 2010)

(untitled) - Lin, Z.-W.; Tsao, Y.-C.; Yang, M.-Y.; Huang, M. H. (Chem. – Eur. J., 2016)

(untitled) - Baskaran, A.; Smereka, P. (J. Appl. Phys., 2012)

(untitled) - Semenova, A. A.; Ivanov, V. K.; Savilov, S. V.; Goodilin, E. A. (CrystEngComm, 2013)

(untitled) - Sidorov, A. V.; Grigorieva, A. V.; Goldt, A. E.; Eremina, O. E.; Veselova, I. A.; Savilov, S. V.; Goodilin, E. A. (Funct. Mater. Lett., 2016)

(untitled) - Hoflund, G. B.; Weaver, J. F.; Epling, W. S. (Surf. Sci. Spectra, 1994)

(untitled) - Mikac, L.; Ivanda, M.; Đerek, V.; Gotić, M. (J. Raman Spectrosc., 2016)

(untitled) - Nie, S.; Emory, S. R. (Science, 1997)

(untitled) - Tao, A.; Kim, F.; Hess, C.; Goldberger, J.; He, R.; Sun, Y.; Xia, Y.; Yang, P. (Nano Lett., 2003)

USADA database

(untitled) - Shull, E. R.; Wood, J. L.; Aston, J. G.; Rank, D. H. (J. Chem. Phys., 1954)